Direct growth of urchin-like ZnCo2O4 microspheres assembled from nanowires on nickel foam as high-performance electrodes for supercapacitors. (1st July 2015) - Wu, Chun; Cai, Junjie; Zhang, Qiaobao; Zhou, Xiang; Zhu, Ying; Li, Lingjun; Shen, Peikang; Zhang, Kaili
Graphical abstract: Conductive nickel foam supported urchin-like ZnCo2 O4 microspheres composed of ultrafine nanowires with superior supercapacitive performance have been achieved. Highlights: Conductive Ni foam supported urchin-like ZnCo2 O4 microspheres have been prepared. ZnCo2 O4 microspheres possess large specific surface area and mesoporous structure. The ZnCo2 O4 microspheres show excellent supercapacitive performance. Abstract: Urchin-like ZnCo2 O4 microspheres grown on nickel foam have been successfully prepared by a two-step facile strategy involving hydrothermal method and subsequent thermal annealing treatment. The as-obtained nickel foam supported urchin-like ZnCo2 O4 microspheres can be directly used as the electrodes for the supercapacitors. The physical characterizations indicate that the hierarchical urchin-like ZnCo2 O4 microspheres are composed of numerous nanowires and have a large specific surface area of 84.8 m 2 g −1, which are beneficial for the electron and ion transport and the increase of electroactive surface areas. In addition, the electrochemical properties of the urchin-like ZnCo2 O4 microspheres as binder-free electrode for supercapacitor are studied by cyclic voltammetry, current charge-discharge, electrochemical impedance spectroscopy, and cycle life measurements in 6 M KOH electrolyte. The urchin-like ZnCo2 O4 microspheres electrode exhibits a high capacitance of 1841.8 F g −1 at a current density of 1 A g −1 and keeps the capacitance retention about 78.4% at 10 A g −1 . After 3000 cycles, the specific capacitance is about 1390.1 F g −1 at a current density of 10 A g −1, and it also shows the excellent cycling stability (95.8%). All the results demonstrate that the urchin-like ZnCo2 O4 microspheres supported on nickel foam have great potential as high-performance electrodes for supercapacitors.